Repensar la democracia participativa en el Perú - Vásquez Castillo, Yeison (2021)
In Peru, participatory democracy includes descriptive notions, typical of deliberative democracy, a concept that has not been developed, and that could be the cause of its attrition and incorrect operation. This article questions the emergence and institutionalization of participatory democracy and proposes a research framework that allows identifying the quality of participation and deliberation. Finally, some guidelines are given that seek to lay the foundations for an approach that restructures citizen participation: Engineering of citizen participation.